Stabilization of Soft Kaolin Clay with Silica Fume and Lime - Alrubaye, Ali Jamal; Muzamir, Hasan; Mohammed, Y. Fattah (Taylor & Francis, 2017)
Studies on chemically stabilised soils have shown that the effectiveness of treatment is largely dependent on the soil’s natural environment. This type of soil can be categorised as problematic due to its weak properties. At the preliminary stage, soft clay soil does not meet the requirements necessary for construction purposes because the entire load from the top of the building will be transferred to the underlying soil. This research considers the soil stabilisation of a soft clay soil (Kaolin S300) stabilised with various percentages of lime and 4% silica fume. The percentages of lime vary at 3, 5, 7 and 9%, while the percentage of silica fume is fixed at 4%. The main objective in this research is to improve the undrained shear strength of soft clay soil mixed with various percentages of lime (L) and 4% silica fume (SF). The properties of the soils were compared for kaolin only and for different percentages of lime mixed with 4% silica fume. The results showed that the optimum percentages of lime and silica fume with respect to the maximum shear strength occurred at 5 and 6%, respectively. The soil–L–SF mix increased the shear strength and angle of internal friction compared to soil–lime and soil–SF mixes because the pozzolanic reaction between lime and SF was more effective with soil particles. The optimum percentage for enhancing the shear strength and the angle of friction was 7–4% L–SF.